A model to support the equitable development of academic literacy in institutions of higher education. Issue 8 (14th September 2022) - Murray, Neil
ABSTRACT: The globalisation of higher education and the resultant increase in the cultural and linguistic diversity of the student body has cast the spotlight on English language proficiency as never before. How universities best assess applicants' linguistic suitability for their future degree studies, set appropriate proficiency thresholds, and put in place suitably structured, relevant and equitable language support post-entry is both an educational question and a moral one. This article looks specifically at English language support post-entry – widely referred to as in-sessional support – and considers a range of issues concerning the focus of that support and the nature of its delivery. It goes on to describe a decentralised model of English language provision that reflects an academic literacies perspective according to which English language development is inseparable from the acquisition of discipline knowledge. The model, implemented in Australia, rests on the idea that decentralised English language support in the form of faculty-based 'satellite' English language teams promotes relevance and thus engagement and learning. Furthermore, its scalability and cost-effectiveness help ensure that it is sustainable.